Aktivitas Inhibisi Pertumbuhan Plasmodium falciparum dan Micobacterium tuberculosis dari Ekstrak dan Partisi Klika Kayu Jawa (Lannea coromandelica [Houtt.] Merr.) - Nursalam Hamzah; Nurhidayah Wahid; Muh Ihsan; Nur Syamsi Dhuha; Karnila Amir Tahir; Alifia Putri Febrianti; Isriany Ismail (Jurnal Farmasi dan Ilmu Pengobatan, 2017)
Malaria and tuberculosis are two diseases with high prevalence in Indonesia. The treatment has a problem because some types of plasmodium and mycobacterium resistance with antituberculosis and antimalarials which are used today. To solve this problem, exploration to create a new drug must be done. Kayu jawa (Lannea coromandelica [Houtt.] Merr.) is one of the plants commonly used as a traditional medicine for curing malaria and tuberculosis. This research aimed to explore the antimalaria dan antituberculosis of L. Coromandelica. The procedure begins with the extraction of stem bark with methanol, then partitioned by solid-liquid extraction to found soluble and insoluble hexane partitions. Both extract and partitions were tested for anti-plasmodium activity by Desjardins method and antituberculosis by MODS method. The result showed that all samples can inhibit Mycobacterium tuberculosis growth and also Plasmodium falciparum. In conclusion, L. Coromandelica has a potential to developed as antimalaria and antituberculosis drug.